The Principle of People's Authoritative Manifestation in Mining Management: An Inclusive Legal Perspective - Muchamad Taufiq; Fradhana Putra Disantara (SASI, 2023)
Introduction: Principle of the people's authoritative manifestation in mining activities must be a reference and guide by the state in formulating policies related to mining management.